Effectiveness of a multicomponent intervention to reduce social isolation and loneliness in community‐dwelling elders: A randomized clinical trial - Hernández‐Ascanio, José; Perula‐de Torres, Luis Ángel; Rich‐Ruiz, Manuel; González‐Santos, Josefa; Mielgo‐Ayuso, Juan; González‐Bernal, Jerónimo; Roldán‐Villalobos, Ana María; Pérula ‐ de Torres, Carlos; Fernández‐Márquez, Rodrigo; Dios‐Guerra, Caridad; Urbano‐Priego, Manuela; Luna‐Morales, Silvia; et al. (Nursing open, 2023)
Aims To assess the effect of a multicomponent intervention on reducing social isolation and loneliness and improving the quality of life in community‐dwelling older adults. Design A cluster‐randomized controlled clinical trial. Methods A total of 56 older adults participated in the control group and 63 older adults in the experimental group. The intervention consisted of 6 home‐based face‐to‐face sessions, intercalated with 5 telephone calls and was conducted by nursing students and volunteer staff with experience in the subject. The study was conducted between April 2018 and December 2019. In terms of statistical analysis, several procedures were carried out: a statistical analysis per protocol and intention to treat, considering isolation, loneliness and quality of life as endpoints; a comparison of paired means, to analyse the behaviour of the outcome variables at baseline and the end of the study; and finally, a binary logistic regression analysis, considering social support as a dependent variable. Results The study results do not show the effectiveness of the modified CARELINK programme, analysed as a whole, on the decrease in social isolation or loneliness or the improvement in HRQL. However, a detailed analysis of the behaviour of some of the variables during the study indicates some results that deserve to be commented on. Comparing the mean confidential support scores between the experimental and control group at the initial and final stages shows significant differences in the analysis by protocol, and close to statistical significance in the analysis by intention to treat. Comparing the paired means obtained in the experimental group, an improvement in emotional loneliness scores was found. Finally, the variables associated with the social support of the subjects at the end of the follow‐up period were as follows: having people who help them and mobility. Conclusion Although the results obtained do not allow us to affirm that the intervention programme is effective, these same results point to improved confidential support and emotional loneliness in older adults participating in the intervention. Having people to help them and a greater degree of mobility are factors favouring the decrease in social isolation. Impact This study suggested that modified CARELINK, a multicomponent intervention performed by trained volunteers, could improve confidential support in community‐dwelling older adults. It also reports the importance of considering the level of mobility and support networks as determinants of the improvement caused by the intervention.